MAQASID SYARIAH IN THE INFLUENCE OF MOTIVATION AND PERCEPTION ON BRAND LOYALTY AND ITS IMPLICATIONS IN THE FINANCING DECISIONS - Sarwoto Sarwoto; sugianto sugianto; Hermansyah Alam (Proceeding International Seminar of Islamic Studies, 2022)
This research was conducted in 3 (three) branch offices of PT Bank Syariah Indonesia (Persero) Tbk in North Sumatra. They are Tebing Tinggi City, Serdang Bedagai Regency, and Batu Bara Regency. The number of respondents is 200 respondents. They are MSME customers with the collectability of current financing. The sampling method used is accidental sampling. This research intends to know the view of maqasid sharia in the influence of motivation and consumer perceptions of brand loyalty and its implications for financing decisions. The Research is done by using SEM model, data processing with PLS 3.0 smart software. The research answers the influence of motivation and perception on brand loyalty and its implications for financing decisions for MSME customers. The research also reveals the maqasid sharia view of the research results.Keywords : Motivation, Perception, Brand Loyalty, Financing Decisions, Maqasid Sharia